The effects of preferential trade agreements (PTAs) on international trade flows - Guo, Jianzhi (Kansas State University, 2021)
This report considers the effects of preferential trade agreements (PTAs) on bilateral trade flows. First, it describes the evolution of PTAs since the end of WWII, noting that PTA formation has trended upward since the late 1980s. As of April 2021, there are 349 active PTAs in force. However, international trade economists have only recently developed empirical strategies to consistently estimate the average effect of a PTA on bilateral trade. Baier and Bergstrand (2007) showed that - after accounting for endogeneity bias using panel techniques - PTAs had much greater effects on bilateral trade flows than was previously suggested in the literature.
Keywords: International trade; Free trade agreements; Preferential trade agreements; Heterogeneous effects; Trade policy